EFFECT OF CONTACT TIME ON BIOSORPTION OF LEAD (II) METAL IONS USING SIJONTIAK FRUIT RIND (BACCAUREA POLYNEURA) - Nailatul Fadhilah; Desy Kurniawati (Sean Institute, 2023)
Lead is the fifth most dangerous heavy metal contained in industrial wastewater and its presence need to be handled properly. Biosorption is one method that can be used to reduce heavy metal levels ions contained in the wastewater. Sijontiak peel is used as a biosorbent to absorb water lead metal because it has the potential as a biosorbent and its use is still minimal in society. Sijontiak skin uses NaOH activator as an absorber for Pb+2 metal ions batch method. In this study, we determine the effect of contact time on metals lead absorption. The results showed that the optimum adsorption time for Pb2+ metal ions was at a contact time of 90 minutes with an absorption capacity of 17.5375 mg/g.